Political Cults as a New Phenomenon of Religious Studies - Silayeva, Zoya Vladimirovna (Journal of History Culture and Art Research, 2017)
The article investigates the study of political cults, the emergence of which is the result of ongoing processes in the religious sphere in the post-secular period. These processes include the active formation and development of new religious movements and politicization of the religion. The growth of their influence is due to a number of reasons. Firstly, the post-Soviet period was characterized by a crisis of religious and national identity, which facilitated the growth of people’s interest in the non-traditional religiosity. Secondly, there was an increase in the desire of religious groups to participate in the political process by any means in the 90s. As a result, such processes generate a controversial phenomenon of "political cult". This article includes an attempt to consider and analyze the approaches to the definition of the "political cult" concept available in the current literature. To this end, we have chosen a systematic approach that enables, considering the constructivist and instrumental features of this phenomenon, to consider it from the point of view of a structural, functional and strategic model. This approach made it possible to identify specific features of the political cult, distinguishing it from political parties and individual religious-political entities.